An encapsulation of phosphorus doped carbon over LiFePO4 prepared under vacuum condition for lithium-ion batteries. (February 2021) - Li, Yin; Wang, Li; Zhang, Keyu; Liang, Feng; Yuan, Meimei; Zhang, Hui; Yao, Yaochun
Abstract: In this study, nano-sized LiFePO4 (LFP) is prepared by employing biomass of phytic acid (PhyA) as a novel phosphorus source to replace traditional phosphoric acid. To further improve its electrochemical performance, carbon coating and phosphorus-doped strategy are proposed via two-step vacuum sintering process with sucrose and triphenylphosphine (TPP) as carbon and phosphate source, respectively. Doping the phosphorus is effective to improve the graphitization of carbon and can greatly enhance electrical conductivity and mobility of lithium ions, achieving superior cycle stability and high rate capacity of the phosphorus-doped composite. The LFP/P0.25 -C exhibits higher discharge capacities (130.2 mAh g −1 ) than the pristine LFP/C (112.3 mAh g −1 ) at 10C and excellent cycling performance, delivering capacity retention above 97% after 200 cycles at 1C, while the LFP/C is only 91%. Therefore, we believe that the high capacity and superb cycle stability are the results of unique features of nano-sized LFP assisted by coating phosphorus doped carbon. Highlights: Hierarchical LiFePO4  was prepared by using biomass of PhyA. P-doped carbon decorated LiFePO4 with different contents has been fabricated. P-doped carbon increases the electrons and ions diffusion rate.